EU's eastern neighbours: Institutional harmonisation and potential growth bonus - Artur Radziwill; Paweł Smietanka (Center for Social and Economic Research (CASE), 2009)
This paper provides the quantitative estimate of the potential growth bonus for CIS countries, and in particular EU's Easter Neighbours, that can be a result of deeper institutional harmonisation with the EU. Econometric investigation involving instrumental variable, simultaneous equation and dynamic panel techniques documents the strong positive link between growth performance and reforms, as well as between reforms and European integration. The paper derives the range of possible values of growth bonus from the deepened neighbourhood cooperation between 1 and 3.8 with the median at 1.8 percentage points. The least growth bonus is expected through basic liberalization reforms, while countries with a considerable institutional gap are likely to gain the most.
Keywords: F59; O19; O49; O57; P21; P26; P27; 330; institutions; reform; growth; transition; integration; neighbourhood; dynamic panel; Institutioneller Wandel; Wirtschaftswachstum; Europäische Integration; Wirtschaftsintegration; EU-Nachbarstaaten; GUS-Staaten; EU-Staaten